2018
DOI: 10.3390/su10061966
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sustainability as Innovation Objectives on Innovation Efficiency

Abstract: Though sustainability exists as major objective of pursuing innovation, the effect of it on innovation performance is still unanswered. While the outcome of innovation should consider both input and output, moreover, studies on sustainable innovation are yet to consider the overall efficiency, but rather the performance itself. To fill the gap between the effect of sustainability as the objective of innovation and its innovation performance, and to bridge the hole between the outcome of sustainable innovation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 51 publications
(77 reference statements)
0
28
0
4
Order By: Relevance
“…Chen et al [101] developed a dynamic analytical framework of regional R&D efficiency systems, considering the dynamic interdependence between regional R&D activities over different periods, and they ascertained that eastern China had a higher efficiency than other provinces. To date, the relationship between sustainable innovation and innovation efficiency has been vague [70]. Several researchers have paid attention to the performance and efficiency of sustainable innovation.…”
Section: Regional Sustainable Innovation Efficiency Evaluationmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen et al [101] developed a dynamic analytical framework of regional R&D efficiency systems, considering the dynamic interdependence between regional R&D activities over different periods, and they ascertained that eastern China had a higher efficiency than other provinces. To date, the relationship between sustainable innovation and innovation efficiency has been vague [70]. Several researchers have paid attention to the performance and efficiency of sustainable innovation.…”
Section: Regional Sustainable Innovation Efficiency Evaluationmentioning
confidence: 99%
“…Several researchers have paid attention to the performance and efficiency of sustainable innovation. Shin et al [70] calculated the innovation efficiency of Korean companies, considering sustainability through a DEA method, and found that environmental improvement could negatively affect innovation efficiency. Wang et al [21] studied the innovation efficiency of green performance in 29 sectors of China's manufacturing industry, and found a shift to green innovation in these sectors.…”
Section: Regional Sustainable Innovation Efficiency Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The objectives of sustainable innovation could be categorized into several components depending on literature, previous studies included reduction of raw material and energy consumption as key sustainability-related objective in common. Kunapatarawong and Martínez-Ros [11] divided sustainability-related objectives into: (1) reducing material usage, (2) reducing energy usage, (3) mitigating environmental impact, and (4) complying with the environmental requirements, while Shin et al [23] categorized sustainability-related motivations into three: reduce material and energy, improve environment, and improve safety of workers or environment of their workplace. Moreover, Poussing [24] argued that: (1) reduction of material and energy cost and (2) reduction of environmental impact are two environment-related innovation objectives, and Ulvenblad et al [25] classified maximization of material and energy efficiency as one of the major sustainable business model archetypes.…”
Section: Materials and Energy Reduction As Innovation Objectivesmentioning
confidence: 99%
“…Since innovation does not represent a linear process [17], the innovation feature of energy projects, by its very nature, contains elements of non-linearity or nonlinear behavior (for example, technical systems when operated close to saturation). Creativity is often brought in connection with a chaotic, experimental, unpredictable atmosphere, and poorly structured process [18], therefore engaging more people in the creative processes does not necessarily mean achieving better energy performances.…”
mentioning
confidence: 99%